GANGGUAN MENTAL PADA MAHASISWA YANG MENJADI FAKTOR AKIBAT TERJADINYA BUNUH DIRI - Azka Safarah Ludisti Mauliani; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
This study discusses the relationship between mental disorders in college students and factors related to suicide. Mental disorders are conditions that can affect daily thoughts, feelings and behavior. Mental disorders can include depression, anxiety disorders, bipolar disorder and others. There are also various kinds of mental disorders and they can affect each individual differently. Students themselves can experience different mental disorders, such as stress, anxiety disorders and depression. The consequences that can occur if someone experiences a mental disorder can vary, starting from small things to things that can have very fatal consequences. From small things, mental disorders can cause someone to distance themselves from their surroundings, if they lead to bigger things, mental disorders can cause someone to commit suicide. This study is very interesting to discuss because it aims to answer the following questions: (1) How can a student suffer from mental disorders? (2) How can mental disorders influence a student to commit suicide?